HD 158450: A MAGNETIC CHEMICALLY PECULIAR STAR IN A YOUNG STELLAR GROUP - Drake, N. A.; Jilinski, E. G.; Ortega, V. G.; Reza, R. de la; Bazzanella, B. (Одеські астрономічні публікації, 2008)
We report on the discovery of the Zeeman resolved spectral lines, corresponding to the very large magnetic field modulus [H] = 11.1 kG, in the spectrum of the chemically peculiar star HD 158450 belonging to the recently discovered Mamajek 2 stellar group. We determined fundamental parameters and projected rotation velocity of the star. Dynamical 3D mean orbit calculations showed that Mamajek 2 stellar group has an age of 135+-5 Myr. Based on this age, we estimate that HD 158450 has completed about 12of its main-sequence life. The importance of the detailed study of HD 158450, a member of a stellar group with a well determined age, for understanding the origin and evolution of stellar magnetic fields is discussed.